The Relationship of Self-Regulation with Obedience to School Regulations - Dila Tri Buana Dewi; Taufik Taufik (Universitas Negeri Padang, 2020)
Self-regulations forms the ability to control behavior with cognitive abilities to that individuals can react in the environment. Self-regulations, among other, can be aimed at obedience to school regulations for students who are undergoing a developmental stage at the educational level. Obedience to school rules requires internal regulatory abilities that come from rational considerations, conscience and desire. This study aims to reveal the description of the relationship between self-regulation and compliance with school regulations in students of SMK N 1 Pariaman, West Sumatera. This research isa descriptive correlations study, with a sample of 177 students, obtained by distributing online questinnaires using google forms, using stratified propotional random sampling technique. The data collections instrument used a likert scala model questionaire. The result showed that most a high level of self-regulations and most students high compliance with school regulations. Furthermore, thet research findings also show that self-regulations and adherence to school regulations have a positive and significant relationship.